Good Agricultural Practices in FPOs and Contract Farming: A Comparative Study - Aruna Kumari A; Kalpana K (Archives of Current Research International, 2025)
The adoption of Good Agricultural Practices (GAP) plays a critical role in improving farm productivity, ensuring food safety, and enhancing market access, particularly in the context of export-oriented crops like chilli. This study investigates the extent and economic implications of GAP adoption among chilli farmers in Andhra Pradesh across three different farming models: Farmer Producer Organizations (FPOs), contract farming, and non-contract farming. A total of 135 farmers were randomly selected from the NTR, Prakasam, and Kurnool districts for comparative analysis using an adoption index and Garrett’s ranking technique. The results revealed that 73.33% of FPO farmers exhibited a high level of GAP adoption, while medium adoption was more prevalent among contract (68.89%) and non-contract (48.89%) farmers. The major drivers of chilli cultivation were soil-climate suitability, market demand, and higher returns. Conversely, high input costs and limited knowledge were the primary constraints to GAP adoption, especially among non-contract farmers. FPOs significantly outperformed other models in terms of compliance with certified inputs, integrated pest and crop management, and hygienic post-harvest handling. The findings underscore the importance of promoting GAP through institutional mechanisms, capacity building, and supportive policy frameworks to scale sustainable chilli production and enhance farmers’ economic resilience.